2013
DOI: 10.1111/vru.12028
|View full text |Cite
|
Sign up to set email alerts
|

NORMAL REGIONAL DISTRIBUTION OF CEREBRAL BLOOD FLOW IN DOGS: COMPARISON BETWEEN 99mTc‐ETHYLCYSTEINATE DIMER AND 99mTc‐ HEXAMETHYLPROPYLENE AMINE OXIME SINGLE PHOTON EMISSION COMPUTED TOMOGRAPHY

Abstract: Functional imaging provides important insights into canine brain pathologies such as behavioral problems. Two (99m) Tc-labeled single photon emission computed tomography (SPECT) cerebral blood flow tracers-ethylcysteinate dimer (ECD) and hexamethylpropylene amine oxime (HMPAO)-are commonly used in human medicine and have been used previously in dogs but intrasubject comparison of both tracers in dogs is lacking. Therefore, this study investigated whether regional distribution differences between both tracers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Mean differences in L/NT (lesion to normal tissue) were used to estimate relative changes of rCBF, as previously reported [19,20]. This study showed that local mild hypothermia therapy could significantly increase rCBF as assessed by SPECT imaging at day 7 in ICH patients.…”
Section: Discussionmentioning
confidence: 52%
“…Mean differences in L/NT (lesion to normal tissue) were used to estimate relative changes of rCBF, as previously reported [19,20]. This study showed that local mild hypothermia therapy could significantly increase rCBF as assessed by SPECT imaging at day 7 in ICH patients.…”
Section: Discussionmentioning
confidence: 52%
“…Regional cerebral blood flow was evaluated with SPECT using the 99m Tc-labelled tracer HMPAO (d, 1, hexamethylpropylene amine oxime, Ceretec, GE healthcare LTD, UK). This is a validated technique to study rCBF in dogs [ 40 , 41 ] . The lipophilic tracer passes the blood brain barrier and is taken up by neurons, in a manner proportionally to cerebral blood flow and neuronal function.…”
Section: Methodsmentioning
confidence: 99%
“…The lipophilic tracer passes the blood brain barrier and is taken up by neurons, in a manner proportionally to cerebral blood flow and neuronal function. In the neurons, it is transformed into a hydrophilic form and becomes trapped intracellular [ 40 ] . After dexmedetomidine premedication, a cephalic catheter was placed and the tracer was administered intravenously (30.9 MBq/kg ± 3.0 MBq).…”
Section: Methodsmentioning
confidence: 99%
“…It was hypothesized that the PI, at the stimulation site would differ significantly (α = 0.05) for each stimulation condition. [ 99m Tc]HMPAO SPECT (Single Photon Emission Computed Tomography; d, 1, hexamethylpropylene amine oxime) scans were used to semi-quantify the perfusion indices (PI) of the cortical, cerebellar, subcortical areas and the olfactory bulb [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%